Proximal tibial osteotomies for treating grade IV medial patellar luxation in two feline stifles - Silva, Gabriela Mariano da; Carrera, Alefe Luiz Caliani [UNESP]; Cunha, Olicies da; Minto, Bruno Watanabe [UNESP]; Curuci, Eloy Henrique Pares (Elsevier, 2025)
Objectives: There is a lack of literature regarding the surgical management of high-grade patellar luxation in cats. Among the available options, corrective osteotomies are suitable for correcting severe bone deformities. Therefore, this study aimed to report on the surgical management of grade IV medial patellar luxation (MPL) through tibial corrective osteotomies in two cats. Material and Methods: The two cats were diagnosed with grade IV MPL. The marked alterations observed in radiographic and tomographic images indicated external tibial torsion of 15.7° and 21.8°, concomitant with tibial valgus of 13.9° and a tibial plateau angle (TPA) of 20°, respectively. For surgical treatment, chrondoplasty was performed in Case 1, and block recession trochleoplasty in Case 2, followed by a combination of techniques originally developed for dogs. Proximal total tibial osteotomy (PTO) was combined with medial crescentic closing wedge osteotomy (MCCWO) for one case and with cranial closing wedge ostectomy (CCWO) for the other case. Results: Satisfactory postoperative results were obtained for both cats, resulting in realignment of the stifle extensor mechanism, with both tibial torsions close to 0° in subjective analysis. Additionally, a mechanical medial proximal tibial angle of 91° and a mechanical medial distal tibial angle of 99.3° were achieved for the first cat, whereas a TPA of 9.2° was achieved for the second cat. No major complications were observed, and the cats showed an early return to weight-bearing on the affected limb. Conclusion: Both cases highlight that tibial corrective osteotomies are suitable for cats and may play a role in the decision-making process for treating high-grade MPL. Moreover, a combination of PTO with MCCWO or CCWO may help achieve satisfactory outcomes.
Keywords: Corrective osteotomy; Feline; Medial patellar luxation; Surgery; Tibial torsion; Tibial valgus